Characterization of the energy and angular dependence of optically stimulated dosimeter responses in broad beam neutron radiation fields - Conde, Jonathan Carlos (Kansas State University, 2024)
Personal dosimeters are used in facilities where occupational radiation doses may exceed 10% of the annual radiation worker dose limit (10 CFR § 835.402, 10 CFR § 20.1502). In years past, the Panasonic UD-809 dosimeter was the preferred choice for neutron albedo dosimetry within Department of Energy (DOE) facilities [1]. However, the advent and increasing operational acceptance of Optically Stimulated Luminescence (OSL) dosimeters have shifted preferences toward Landauer's OSL-N model, particularly in DOE and Nuclear Regulatory Commission (NRC) licensed facilities [2]. Studies in the early 2000s examined the angular response of the UD-809 dosimeters from select mono-energetic neutron sources [3]. This study builds on that earlier work by modeling the expected energy and angular responses from Landauer’s OSL-N from multiple mono-energetic neutron fields using the Monte-Carlo N-Particle (MCNP) transport code [4]. The objective is to refine the existing assessment framework by integrating modern Monte-Carlo methodologies and current dose quantification techniques. The aim is to enhance the accuracy of personal dosimeter and facility area monitoring systems, especially with the introduction of OSL dosimetry. This study compares the effect of angular responses with the operational dosimetry quantity ambient dose equivalent, H*(10), used in Facility Area Monitoring (FAM), and the personal dose equivalent, Hp(10), used in individual monitoring. Results show that at increasing incident angle, the theoretical dosimeter response is significantly depressed compared to the dose that would be imparted to a real-world individual or real-world FAM phantom. This effect is exaggerated at lower neutron energies (near thermal), where the dosimeter response may poorly quantify the dose to personnel. At higher neutron energies above 1 MeV, a resonance effect is observed where dosimeter response is relatively constant within certain angular domains. These insights underscore the need to consider the primary incident angle of neutron radiation when processing dosimeter results to properly quantify and assign dose to workers or members of the public. Further, it is shown that at angles coinciding with radiation fluence from the posterior to the anterior, use of facility area monitors with phantoms may provide results that underestimate the dose imparted if corrective measures are not implemented to account for the dominant fluence vector.
Keywords: Dosimetry; Angular dependence; Energy dependence; Neutron radiation; Optically stimulated luminescence